Estudio del fitoplancton aguas arriba y aguas abajo del embalse Casa de Piedra, río Colorado (La Pampa, Argentina) - Galea, M. J. (2014)
In order to study the phytoplankton composition of the Colorado river, seasonal samples were taken during the period between May 2010 and April 2011. The study area is a natural border basin of the provinces of La Pampa and Río Negro and a transitional basin of Patagonia Argentina without records of previous studies. Selected sampling points are located upstream and downstream of the dam reservoir Casa de Piedra. In this study are presented preliminary results of phytoplankton composition analized in emplaced sites at 38º01’58”S-67º52’90”W to 288 msnm and 38°14’55’’ S-67º11’49’’W to 232 msnm. Samples were collected with plankton net of 20 μm mesh size and physicochemical variables were recorded simultaneously. Phytoplankton samples were observed in vivo and then fixed in 4% formalin and embedded in the herbarium of the SRFA UNLPam. As a result of the qualitative study so far hundred forty-one taxa were reported, of which twenty-nine belong to Cyanophyceae, fourty five to Chlorophyceae and fifty five to Bacillariophyceae. The index of similarity of Bray Curtis with S= 48 separates the sampled sites. The greatest similarity is between summer and autumn of 2011 with S = 66.66. Among the common species of Bacillariophyceae, with Aulacoseira granulata var. angustissima, Melosira varians, Fragilaria crotonensis, Cocconeis placentula var. euglypta, Epithemia sorex, Nitzschia sigma, N. sigmoidea and Cymatopleura solea were the highest percentage of occurrence at the study sites. Our results represent a great advance in the knowledge and distribution of algae in this region of the country.